Applied Statistic in Assessing Benefits of Biogas Solutions for Pig groups in Livestock Farm - Thị Quỳnh Hương, Nguyễn (VNU Journal of Science: Earth and Environmental Sciences, 2017)
This paper presents the results of the benefit of biogas solution in wastewater treatment system and the application of mathematical statistical methods to evaluate the benefits of this method for pig groups in concentrated pig farms in Hanoi, Bac Giang, Hoa Binh, Nghe An and Ha Tinh. The results of 8 pig farms in those localities idicate the potential revenue benefits from the sale of greenhouse gas emissio ns credits, save money for electricity and reduce environmental protection fee for the waste water from each group of pigs at different stages of growth (pregnant sows, sows, piglets and porkers). The average annual value of pregnant sows is 146.611 ± 37.718 VND, 126.424±68.920 VND for sows, 155.405 ±64.414 VND for piglets and 122.680 ±61.217 VND for porkers (confident interval is 68.2%). The initial results of this study show that the statistical method was applied effectively to solve environmental problems, and also provide useful information to propose solutions to improve the efficiency of the biogas system inmanagement of waste and biogas use to reduce greenhouse gas emissions and save energy.